Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai Pada PT. Bintang Pinang Cemerlang Kota Jambi - May May (Universitas Batanghari Jambi, 2022)
Work motivation plays a very important role in employee performance. Therefore, the purpose of this research is to describe the work motivation and employee performance, and to find out and analyze the effect of work motivation on employee performance in PT. Bintang Pinang Cemerlang Kota Jambi. Research methods in this study is descriptive and quantitative method. Data analyze use SPSS Ver 22 and using models simple linier regression with result of count Y = 1,116+0,527X+e. The test of determination with R2 of 37,6%. T test by comparison tcount 3,547 > ttable 0,3338 then Ho accepted Hi be. Rejected. To analyze the effect of work motivation on employee performance on PT. Bintang Pinang Cemerlang Kota Jambi. The distribution of questionnaires with a then the sample in this study amounted to 35 people respondent. Work Motivation regression coefficient (X) is 0,527, meaning that work motivation (X) has increased by 1%, so employee performance (Y) PT. Bintang Pinang Cemerlang Kota Jambi. The coefficient of determination is known from the value of R2=0,376 (37,6%) which means that work motivation (X) is able to explain employee performance (Y) at the PT. Bintang Pinang Cemerlang Kota Jambi that is equal to 37,6% and the remaining 62,4% is influenced by other variables. Not investigated in this study. Based on t-test, t-count value is 3,547 and the t-table is 0,3338. From the comparison results, it can be seen that the test by comparison tcount 3,547 > ttable 0,3338 then Ho accepted Hi be. Rejected. Meaning that brand image affect purchasing decisions at PT. Bintang Pinang Cemerlang Kota Jambi.